EPRL/FK group field theory - Ben Geloun, Joseph; Gurǎu, Rǎzvan; Rivasseau, Vincent (epl, 2010)
The purpose of this note is to clarify the group field theory vertex and propagators corresponding to the EPRL/FK spin foam models and to detail the subtraction of leading divergences of the model.
Published online 21 January 2011
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 30.09.2022